Pelatihan Java Fundamental di SMKN 1 Balikpapan - Rahman, Aswadul Fitri Saiful; Irfan, Muhammad; Muslimin, Imam (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
SMK Negeri 1 Balikpapan is one of the favorite vocational schools in the Sepinggan village, South Balikpapan. In the era of the industrial revolution 4.0 which is increasingly developing, technology is increasingly influential in every life, including in the world of education. From these considerations, an idea arose to provide Fundamental Java programming training to students of SMK Negeri 1 Balikpapan to be equipped as Java programmers who are reliable and able to compete in the world of work. This training was held at SMKN 1 Balikpapan in the IT department which includes TKJ and RPL. The training was carried out for 2 days by a lecturer in Electrical Engineering at the University of Balikpapan. Students directly practice with their respective computers or laptops, In the project session, they succeeded in making project programs individually and in groups.